The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyg.2020.00503
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs Toward Computerized Cognitive Training in the General Population

Abstract: Introduction: In recent years, computerized cognitive training (CCT) programs have been developed commercially for widespread public consumption. Despite early enthusiasm, whether these programs enhance cognitive abilities in healthy adults is a contentious area of investigation. Given the mixed findings in the literature, researchers are beginning to investigate how beliefs and attitudes toward CCT impact motivation, expectations, and gains after cognitive training. Method: We collected survey data from 497 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Several factors are also known to support long-term cognitive training. These include the possession of high behavior control, intrinsic motivation to achieve a goal, and interest in the performed activity, including due to the awareness of the development of cognitive deficits [22,28,47]. Previously, it was shown that when assessing motivational inducers of behavior, older women single out cognitive training as a priority in maintaining their health; however, only 8% of this group actually consistently participated in cognitive training using a battery of computerized techniques [48].…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors are also known to support long-term cognitive training. These include the possession of high behavior control, intrinsic motivation to achieve a goal, and interest in the performed activity, including due to the awareness of the development of cognitive deficits [22,28,47]. Previously, it was shown that when assessing motivational inducers of behavior, older women single out cognitive training as a priority in maintaining their health; however, only 8% of this group actually consistently participated in cognitive training using a battery of computerized techniques [48].…”
Section: Groupmentioning
confidence: 99%
“…Apparently, therefore, the lack of visible success after the first training sessions causes them to refuse further activities. Individualized cognitive training with feedback that reinforces subjective assessments of change can help to improve cognitive self-esteem in older adults [22], and success can help to reduce perceptions of difficulties and become more willing to participate in cognitive activities [50].…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the concerns noted above, CTT has only been growing in popularity (Goghari, Krzyzanowski, Yoon, Dai, & Toews, 2020). As discussed by Hague et al (2020), this raises difficult questions for health psychologists who are asked to provide these services, often by patients and parents who are desperate for any sort of improvement.…”
Section: Evidence-based Practice and Cctmentioning
confidence: 99%
“…These interventions, henceforth referred to as computerized cognitive training (CCT), have surged in popularity in both the general public (e.g., Goghari et al, 2020) and the clinical research literature, with more than $25 million in funding from the National Institutes of Mental Health dedicated to the development or refinement of these treatments in the past year alone (NIH Reporter, 2022). Despite this rapid public uptake and investment of resources, however, 4 there is still considerable debate about whether and to what extent CCTs as a class remain a promising direction for intervention research or a clinically useful resource for patients.…”
mentioning
confidence: 99%